Analisis kemampuan berpikir tingkat tinggi pada siswa introvert dalam menyelesaikan masalah matematika - Nur Laeli Sangadah; Sukarmi (Jurnal Inovasi Pendidikan Matematika (JIPM), 2019)
This study aims to determine the ability to higher order thinking introvert students to solve mathematics problems. This research is a qualitative research with a phenomenological approach. The subjects of this study are students of class VIII A of SMPN 2 Sruweng in the academic year of 2018/2019 totaling 2 students with the subject taken by technique using purposive. Data collection techniques used 3 methods, namely mathematics problem solving tests, field notes and interviews. The research instruments in this study were researchers, mathematics problem solving tests and interview guidelines. Techniques of analysis data used the model of Miles and Huberman which includes three steps, namely data reduction, data presentation, and drawing conclusions. The results of the study are to show the ability to think at a higher order thingking of introvert students in the aspect of analyzing intovert students able to decipher information and use the right strategy so as to obtain a correct answer. Then, in the aspect of evaluating introvert students are able to assess and draw an opinion on the decisions obtained from the results of solving problems.